Indonesia's Disaster Resilience Against Volcanic Eruption: Lessons from Yogyakarta - Prakoso, Septyanto Galan; Wijaya, Abyan Ardan; Putra, Ferdian Ahya Al (KnE Social Sciences, 2022)
Indonesia is the largest archipelago country in the world, with more than 17,000 islands. Located on the “ring of fire”, Indonesia has many active volcanoes, and also has the threat of earthquakes as a result of constant movement of the tectonic plates between the Eurasian and Australian plates. Because of these features, Indonesia has one of the highest disaster-risk of all countries in the world. In terms of disaster resilience, the people of Indonesia have their own cultures with many local communities that have been educated about the potential disasters that might arise. After the 2004 tsunami that hit Aceh, disaster mitigation education gained more attention in Indonesia. Using the concept of disaster risk reduction uniquely fused with local wisdom and culture, this study aimed to describe the potential impact of natural disasters in Indonesia, and the prevention of the loss of life. Qualitative analyses were used, with a focus on Yogyakarta province, as one of the regions in Indonesia with the highest natural disaster risk. This study found that disaster resilience is increasing in Indonesia. Keywords: Indonesia, natural disaster, volcanic eruption, disaster risk reduction, Yogyakarta